Corrosion behavior of laser powder bed fusion manufactured nickel-free stainless steels in high-temperature water - Goel, Sneha; Bojinov, Martin; Capek, Jan; Saario, Timo; Polatidis, Efthymios; Kantonen, Tuomas; Salminen, Antti; Blankenburg, Malte; Ganvir, Ashish; Que, Zaiqing (Elsevier Ltd, 2025)
The paper presents a comprehensive investigation of electrochemical behavior of laser powder bed fusion (PBF-LB/M) nickel-free stainless steels in high-temperature water. The PBF-LB/M nickel-free steels processed with various laser parameters and heat treatments exhibit tunable microstructures. Electrochemical impedance spectroscopy (EIS) indicates a 2–3 times lower oxidation rate for the nickel-free steels compared to wrought 316 L. The outer layer crystallites on nickel-free steels are close to pure Fe oxides. The significantly lower concentration of Ni in the inner oxide and at the alloy/oxide interface account for the important variations of the parameters of water reduction/hydrogen oxidation reactions than wrought 316 L.